Away from fossil-fuels and toward a bioeconomy: Knowledge versatility for public policy?. (September 2017) - Mukhtarov, Farhad; Gerlak, Andrea; Pierce, Robin
In the face of energy security and climate change, and with technological advances, many industrial countries have embraced the transition to a bioeconomy – an economy based on energy, chemicals and materials obtained from biomass. However, the policy and academic discourses on a bioeconomy transition suggest growing controversy around its social, environmental and ethical impacts. In this article, we apply an epistemic forms framework to better understand the scope and extent of the bioeconomy debate. We find that industry and governments take a narrow approach to a bioeconomy and tend to view it exclusively as a technical concept. We argue that the discursive and practical dimensions of the transition would shed light on the issues of what type of a bioeconomy to strive for, through which procedures and with what impacts for diverse stakeholders. We conclude with a set of recommendations related to a bioeconomy transition.